A Novel Text Message Intervention to Improve Adherence to Stimulants in Adults With Attention Deficit/Hyperactivity Disorder. Issue 4 (July 2019) - Biederman, Joseph; Fried, Ronna; DiSalvo, Maura; Woodworth, K. Yvonne; Biederman, Itai; Noyes, Elizabeth; Faraone, Stephen V.; Perlis, Roy H.
Abstract: Background: Attention deficit/hyperactivity disorder (ADHD) is a prevalent neurobiological disorder associated with a wide range of adverse outcomes. Although large data sets document that stimulants decrease the risks for many ADHD-associated adverse outcomes, compliance with stimulants remains very poor. The main aim of this study was to assess the effectiveness of a novel text messaging–based intervention aimed at improving the poor rate of adherence to stimulant medications in adults with ADHD. Methods: Subjects were adults with ages 18 to 55, prescribed a stimulant medication for ADHD treatment. For comparators, we identified at a 5-to-1 ratio (age and sex matched) adult patients from the Partners HealthCare electronic medical record who had been prescribed stimulant medications over a 1-year period. We determined whether patients had timely prescription refills, defined as refilled within 37 days, using prescriptions documented in their electronic medical record. Results: Our results showed that 68% of the SMS intervention group refilled their prescriptions in a timely manner. In contrast, only 34% of patients receiving treatment as usual refilled their prescriptions in a timely fashion (odds ratio, 4.04; 95% confidence interval, 2.49–6.56; P < 0.001). Conclusions: These data indicate that an innovative ADHD-centric text messaging intervention significantly improved patient engagement to treatment with stimulants in adults with ADHD. Findings provide strong support for the use of a readily accessible, inexpensive, and widely available technology to improve the poor rate of adherence to stimulant treatment in adults with ADHD. To the best of our knowledge, this study is the first digital health intervention aimed at improving adherence to stimulant medication for adults with ADHD. Abstract : Supplemental digital content is available in the text.